The Attractions of the Koto Sentajo Tourist Village Destination, Kuantan Singingi Regency - Ahmad Nawawi; Firdaus Yusrizal; Nur Ariniyulia (Sean Institute, 2025)
Kuansing Regency boasts significant tourist attractions. Besides its natural beauty, the area is also rich in historical significance, one of which is Koto Sentajo Village, known as one of the oldest traditional villages in the region. Traces of this history can be seen in the Rumah Godang (Godang House), a historic building estimated to have stood for approximately 1,700 years. Koto Sentajo Tourism Village boasts a diverse range of tourism potential that is no less appealing than other tourist villages. Besides being known as a cultural heritage village, it also boasts a rich natural heritage, which is a unique attraction. This diverse tourism potential makes Koto Sentajo Village a worthy destination for tourists, both local and international. The main attractions that attract tourists to this village include the local customs and traditions, the Rumah Godang (Godang House), a cultural heritage of our ancestors, and the traditional forest, which remains well-preserved. These three features not only reflect local cultural identity but also reinforce Koto Sentajo Village's image as a tourist destination based on local wisdom and environmental preservation. Based on the results of research on the Attraction of Koto Sentajo Tourism Village Destination, Sentajo Raya District, Kuantan Singingi Regency, with a focus on operational variables such as the results of the study show that personal selling and events or sponsorship have an important role in influencing the perception and image of the Koto Sentajo tourism village tourist area. This is because when events or activities are frequently held in the Koto Sentajo traditional village, it will increase the reach of the Koto Sentajo traditional village because every time an event is held there, the tourists who come automatically help promote the Koto Sentajo traditional village destination.